International standards for fetal brain structures based on serial ultrasound measurements from Fetal Growth Longitudinal Study of INTERGROWTH‐21st Project. (1st September 2020) - Napolitano, R.; Molloholli, M.; Donadono, V.; Ohuma, E. O.; Wanyonyi, S. Z.; Kemp, B.; Yaqub, M. K.; Ash, S.; Barros, F. C.; Carvalho, M.; Jaffer, Y. A.; Noble, J. A.; et al.
ABSTRACT: Objective: To create prescriptive growth standards for five fetal brain structures, measured using ultrasound, in healthy, well‐nourished women at low risk of impaired fetal growth and poor perinatal outcome, taking part in the Fetal Growth Longitudinal Study (FGLS) of the INTERGROWTH‐21 st Project. Methods: This was a complementary analysis of a large, population‐based, multicenter, longitudinal study. The sample analyzed was selected randomly from the overall FGLS population, ensuring an equal distribution among the eight diverse participating sites and of three‐dimensional (3D) ultrasound volumes across pregnancy (range: 15–36 weeks' gestation). We measured, in planes reconstructed from 3D ultrasound volumes of the fetal head at different timepoints in pregnancy, the size of the parieto‐occipital fissure (POF), Sylvian fissure (SF), anterior horn of the lateral ventricle, atrium of the posterior horn of the lateral ventricle (PV) and cisterna magna (CM). Fractional polynomials were used to construct the standards. Growth and development of the infants were assessed at 1 and 2 years of age to confirm their adequacy for constructing international standards. Results: From the entire FGLS cohort of 4321 women, 451 (10.4%) were selected at random. After exclusions, 3D ultrasound volumes from 442 fetuses born without a congenital malformation were used to create the charts. The fetal brain structures of interest were identified in 90% of cases. All structures, except the PV, showed increasing size with gestational age, and the size of the POF, SF, PV and CM showed increasing variability. The 3 rd, 5 th, 50 th, 95 th and 97 th smoothed centiles are presented. The 5 th centiles for the POF and SF were 3.1 mm and 4.7 mm at 22 weeks' gestation and 4.6 mm and 9.9 mm at 32 weeks, respectively. The 95 th centiles for the PV and CM were 8.5 mm and 7.5 mm at 22 weeks and 8.6 mm and 9.5 mm at 32 weeks, respectively. Conclusions: We have produced prescriptive size standards for fetal brain structures based on prospectively enrolled pregnancies at low risk of abnormal outcome. We recommend these as international standards for the assessment of measurements obtained using ultrasound from fetal brain structures. © 2020 Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of International Society of Ultrasound in Obstetrics and Gynecology. Contribution: What are the novel findings of this work? Charts of fetal brain measurements in current use are based mostly on small studies with suboptimal methodology and no follow‐up. In this international study, we created standards for the size of five fetal brain structures based on a prospective cohort of fetuses followed up into childhood, demonstrating normal neurodevelopment. What are the clinical implications of this work? Clinical use of such objective fetal brain structure measurements may help to improve the screening and diagnostic performance of prenatal ultrasonography. It should also allow a unified approach to fetal assessment by integration with other standards from the same population and result in a common language when describing aberrations from expected norms.